Antihyperglycemic Activity of Java Tea-Based Functional Drink-Loaded Chitosan Nanoparticle in Streptozotocin-Induced Diabetic Rats - Monita Rekasih; Tjahja Muhandri; Mega Safithri; Christofora Hanny Wijaya (HAYATI Journal of Biosciences, 2021)
Functional drinks containing the leaves of Java tea has been shown to offer many health functionalities, particularly to lower blood glucose levels, due to its bioactive compounds. Nanoencapsulation technology was reported being able to protect these bioactive compounds and also enhance their bioavailability. This study examined the use of nanoencapsulation techniques to improve the bioavailability of Java tea-based functional effervescent drink and enhance its antihyperglycemic activity. Three versions were prepared in this study: ready to drink (RTD) as the control, microencapsulated, and nanoencapsulated. They were all measured for their total phenolic content (TPC) before being tested for their antihyperglycemic activity. The TPC of RTD, microencapsulated, and nanoencapsulated Java tea-based functional drinks (JTFD) were 998,425, 735,433, and 663,517 ppm, respectively. The antihyperglycemic activities were evaluated by feeding each beverage to streptozotocin-induced diabetic Sprague Dawley rats for fourteen days. Nanoencapsulated JTFD was found to be more superior than the other two formulations to decrease the blood glucose level (7.98%), maintain the feed intake, body weight, improve the viability of Langerhans and beta-cells by 49.09%, 32.50%, respectively.